Coronariografia via transradial: Curva de aprendizagem, avaliada por estudo multicêntrico - Labrunie, André [UNESP]; Tebet, Marden Andre; De Andrade, Pedro Beraldo; De Andrade, Mônica Vieira Athanazio; Conterno, Lucieni De Oliveira; Mattos, Luiz Alberto; De Carvalho, Fábio Cardoso [UNESP]; Bregagnollo, Edson Antonio [UNESP] (My University, 2009)
Background: Femoral access for diagnostic and therapeutic coronary procedures has been the dominant approach worldwide, despite an increased risk of vascular and hemorrhagic complications. The transradial approach is a more recent technique used to reduce these complications, providing more comfort and reducing hospitalization costs. However, it is associated with an inherent learning curve. The aim of the study was to evaluate transradial coronary angiography performed by inexperienced operators and compare the success and complication rates of this technique with the classical approach (Sones and femoral), analyzing the influence of the learning curve. Methods: Multicenter, randomized study, in 14 hospitals in São Paulo State in a one-year period. One thousand patients were randomized to the transradial or classical techniques. Results: The success rate was similar in both groups (97.8% vs. 98.5%; P = 0.47). Sones technique was used in 95.2% of the procedures in the classical technique group. The number of catheters used, the duration of the procedure and X-ray exposure were greater in the transradial group (P < 0.001). There were no differences in the major cardiac adverse events (death, infarct and stroke), and vascular and bleeding complications. Operators who had performed over 100 procedures using the transradial approach (3 centers/5 operators) had a lower failure rate (1.6% vs. 3.6%; P = 0.04). Conclusion: A learning period to perform coronary procedures using the transradial approach is required, but it is not associated with an increased risk of procedure failure or vascular complications compared with Sones or femoral approaches.
Transradial coronary angiography: Learning curve, evaluated by a multicenter study
Keywords: Coronary angiography; Learning; Radial artery